The British Southern Cameroons Health Services as an Appendage to Nigerian Health Sector, 1922-1961 - Ngwa, Canute A.; Asongwe, Christian (International Journal of Scientific Research and Management (IJSRM), 2020)
The incidence of disease on the colonial agenda triggered the development of healthcare services by colonial administrations in Africa. In Southern Cameroons, the British administration fashioned a medical policy whose implementation spanned from 1922 to 1930. Informed by the colonial imperative, administrative and medical officers developed medical infrastructure, trained and engaged personnel, conducted research, and made efforts to roll back the incidence of various diseases. This took curative and preventive forms in a context of conflicting agendas, colonial arrogance, cultural ignorance, and defective infrastructure and personnel.  The outcomes were beneficial to the colonial enterprise and detrimental to the economic wellbeing of the local population, the incidental benefits notwithstanding.